PERANCANGAN BUKU ESAI FOTOGRAFI POTRAIT UPACARA YADNYA KASADA GUNUNG BROMO SUKU TENGGER SEBAGAI UPAYA MELESTARIKAN BUDAYA LOKAL - Nempung, Rachmat Isa Asera; Bahruddin, Muh; Fianto, Achmad Yanu Alif (Jurnal ArtNouveau, 2014)
National Park Mount Bromo, has long been recognized by many foreign and domestic travelers. Starting from their destination just for a vacation , see the sunrise , following the Yadnya Kasada ceremony which is held each year, learn Volcanology Mount Bromo. Beside that Yadnya Kasada Ceremony other rituals held at Mount Bromo , include Karo ceremony , ceremony Unan Unan . TheÂ  most attractive ceremony for tourist attention is Kasada ceremony . Kasada in the Tengger tribe is the name of the month , with another name âAsujiâ was the last last month in one year, which is in the Masehi calendar does not always fall in 12 months , due to the Tengger tribe has its own calendar dating system , the average age of his days to 30 days ( respectively - each month rounded ). Tourist destinations of foreign and domestic who came to follow the ritual ceremony Tengger tribe that has been widely recognized , is Yadnya Kasada ceremony held annually . This ceremony every year to experience ups and downs but the number of tourists coming in Kasada always experiencing peak tourist visits . But in fact the Tengger tribe has decreased number of his followers Kasada ritual ceremony . Due to the younger generation who do not follow the ritual ceremony began Yadnya Kasada .